Advances in the Molecular Understanding of Colorectal Cancer - Segelov, Eva (IntechOpen, 2019)
An understanding of the molecular pathogenesis of colorectal cancer by researchers and clinicians is essential to facilitate progress in improving patient outcomes in this common cancer that still carries a poor prognosis if not identified early. This book covers the major areas of importance in the field, incorporating new knowledge that has arisen due to the advancement of molecular techniques and the ability to correlate molecular changes with clinical behaviour of tumours. Each chapter is a summary written by experts, concisely summarising current data as well as highlighting potential areas for advancement. Appreciating the differences between tumours on a molecular level is the key to developing and delivering precision medicine, and nowhere is this more critically required than in the field of colorectal cancer.